Особливості інформаційного забезпечення електронної науки та провідна роль книгозбірень: досвід американських колег - Веретеннікова, Наталія; Кунанець, Наталія (Видавництво Львівської політехніки, 2015)
This article describes the main components of information support of eScience in the USA and emphasizes the leading role of libraries in collecting and preserving information data and the creating of information and communication structure. Also, the basic tasks of the American National Science Foundation and its role in the information society are analyzed.
Keywords: електронна наука; книгозбірня; інформаційно-комунікаційна інфраструктура; інформаційне суспільство